Self-sustained Combustion Synthesis and Asbestos-bearing Waste: Scaling up from Laboratory Towards Pre-industrial Size Plant. (November 2016) - Gaggero, Laura; Caratto, Valentina; Ferretti, Maurizio
Abstract: An apparatus and a technique were developed for triggering the breakdown reaction of chrysotile by means of a combustion synthesis well known as Self-propagating High temperature Synthesis or SHS. The experiments were carried out varying different Asbestos-Containing Waste (ACW). The reactions were carried in a continuous-feeding configuration, indispensable for the development and fine-tuning of the process parameters towards industrial scale up. Experiments demonstrated to be effective in destructing the fibrous habit of chrysotile. The SHS process in comparison with conventional thermal treatments, due to fast reaction time and low activation energy, positively reflects into time and costs of the process.